Sistem Pendukung Keputusan Dengan Metode SAW Untuk Menentukan Guru Terbaik Pada SMK Bina Putra Jakarta - Rizki Armanda; Achmad Udin Zailani (CV. Multi Kreasi Media, 2022)
Teacher is a profession whose emphasis is on functioning as a source and person who provides knowledge for students. SMK Bina Putra Jakarta has the best teacher selection program. However, the process of data collection and selection is still done manually so it is not effective and efficient. Therefore, this research will make a decision support system for determining the best teacher at SMK Bina Putra Jakarta with the simple additive weighting method which aims to make it easier to determine the best teacher. This method has a simple concept, easy to understand, decision alternatives in a simple mathematical form. In this system there are features of teacher data, criteria, grades and teacher rankings as the final result that displays the order of the best teacher rankings. In the final stage, the decision support system was successfully created and tested. The final result of this system is that the highest to the lowest score is obtained and one recommendation is recommended as the best teacher at Bina Putra Vocational School. Based on the test results, all website pages and existing features are as expected and run according to their functions.